An eye for an eye ; Gunless society ; Talking heads [videorecording] - Lazaro, Cheche (The Probe Team, 1990)
Features the death penalty imposition during the kidnap-killing of university students Castanos and Bernabe; proposal to have gunless society and interviews with a horce race caller, a sabong Kristo; stockmarket worker and Shoemart shoe lady.